2014
DOI: 10.1186/1743-0003-11-39
|View full text |Cite
|
Sign up to set email alerts
|

Between-day reliability of centre of pressure measures for balance assessment in hemiplegic stroke patients

Abstract: BackgroundStroke patients have impaired postural balance that increases the risk of falls and impairs their mobility. Assessment of postural balance is commonly carried out by recording centre of pressure (CoP) displacements, but the lack of data concerning reliability of these measures compromises their interpretation. The purpose of this study was to investigate the between-day reliability of six CoP-based variables, in order to provide i) reliability data for monitoring postural sway and weight-bearing asym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
28
2
7

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 42 publications
(89 reference statements)
5
28
2
7
Order By: Relevance
“…Balance problems adversely affect the quality of gait and are closely related to an increased risk of falling [13]. The studies have demonstrated a negative impact of stroke on body balance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Balance problems adversely affect the quality of gait and are closely related to an increased risk of falling [13]. The studies have demonstrated a negative impact of stroke on body balance.…”
Section: Discussionmentioning
confidence: 99%
“…Problem z utrzymywaniem równowagi ciała niekorzystnie wpływa na jakość chodu i jest ściśle związa-ny z podwyższonym ryzykiem upadków [13]. Na podstawie przeprowadzonych badań stwierdzono negatywne oddziały-wanie udaru na równowagę ciała.…”
Section: Dyskusjaunclassified
“…CoP velocity measurements are commonly used in studies focussing on balance in the stroke population [34][35][36]. Participants were asked to stand on the treadmill in most stable standing position with their head straight.…”
Section: Statement Disagree (%) Neutral (%) Agree (%)mentioning
confidence: 99%
“…Es decir, su CoP estará contenido dentro de unárea menor [4]. Buscando medir el balanceo de los pacientes se han examinado métricas basadas tanto en el CoM como en el CoP tratando de relacionarlo con el riesgo de caída y las evaluaciones BBS y TUG [3,[5][6][7]. Algunas de estas pruebas requieren el uso de plataformas de fuerza de alto costo [5], de acceleróme-tros [3,6] o de cámaras [7,8].…”
Section: Introductionunclassified
“…Buscando medir el balanceo de los pacientes se han examinado métricas basadas tanto en el CoM como en el CoP tratando de relacionarlo con el riesgo de caída y las evaluaciones BBS y TUG [3,[5][6][7]. Algunas de estas pruebas requieren el uso de plataformas de fuerza de alto costo [5], de acceleróme-tros [3,6] o de cámaras [7,8]. Estosúltimos implementan sistemas de captura de movimiento, sin marcadores, y modelan al cuerpo como un péndulo invertido con la finalidad de realizar pruebas posturográficas basadas en el movimiento del CoM [7,8].…”
Section: Introductionunclassified